2017
DOI: 10.1111/ijal.12182
|View full text |Cite
|
Sign up to set email alerts
|

Changes in foreign language anxiety: A classroom perspective

Abstract: This article reports the findings of a classroom‐based study whose main purpose was to investigate the changes in the levels of FLA over the course of one semester. In addition, the study sought to understand causes of such changes. The participants were 52 Polish senior high school students, aged 17–19, who were all learners of English. The study encompassed 121 naturally occurring English lessons. The data were gathered by means of questionnaires, interviews and lesson plans. The collected data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 34 publications
1
28
0
2
Order By: Relevance
“…The findings revealed that teachers' anxiety-reducing strategy intervention led to significantly decreased levels of learners' foreign language anxiety. Kruk's (2018) recent investigation showed that language anxiety changes not only over a longer period (i.e., a semester) but also during a single class and from one language lesson to another.…”
Section: Foreign Language Classroom Anxietymentioning
confidence: 99%
“…The findings revealed that teachers' anxiety-reducing strategy intervention led to significantly decreased levels of learners' foreign language anxiety. Kruk's (2018) recent investigation showed that language anxiety changes not only over a longer period (i.e., a semester) but also during a single class and from one language lesson to another.…”
Section: Foreign Language Classroom Anxietymentioning
confidence: 99%
“…For example, such students may avoid class and homework assignments, as well as avoid direct eye contact with their teachers (Horwitz, Horwitz, and Cope 1986;Phillips 1991). Additionally, Kruk's (2018) current investigation showed that language anxiety changes not only over a longer period but also during a single class and from one language lesson to another. Horwitz et al (1991) in Toyama and Kamazaki (2018) described FLA as an individual elaboration of perceptions, insights, apprehensions, faiths, and actions that appears as a phenomenon in a class where someone masters and utilizes foreign languages.…”
Section: Introductionmentioning
confidence: 57%
“…Rezaei and Jafari (2014) found the students' problems in writing such as deficiency and less practice in writing, fear in writing test, fear in getting negative feedback or comment, lack of knowledge, lack of vocabulary, tension indoing perfect work, time limit, and less self-confidence. According Kruk's (2018) investigated 52 Polish senior high school students by using questionnaire, interview, and lesson plan. The study found that English learning anxiety changed along semester either during class or from one language lesson to others.…”
Section: Discussionmentioning
confidence: 99%
“…English learning anxiety can give either positive or negative impacts for the students' achievement. Kruk's (2018) investigated 52 Polish senior high school students by using questionnaire, interview, and lesson plan. The study found that English learning anxiety can change and effect for the students' learning in the semester during class from one language lesson to others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation